Assessment of Diet Diversity among College Students at STIKes Mitra Keluarga - Sartika, Arindah Nur (Journal of Applied Food and Nutrition, 2023)
Students in health college are addressed to have healthy lifestyle, such as having good food habit. Good food habit can be shaped from consuming variety of food. Varied food can prevent nutrient deficiency, one of them is anemia that suffered by one-third women in Indonesia. This study aims to assess diet diversity among college students at STIKes Mitra Keluarga. This study is cross sectional study. About 225 respondents join the study, give information about what their eat during 24 hours, twice, with questionnaire from Minimum Dietary Diversity for Women (MDD-W). The formular consists of 14 food groups and 4 additional groups. The results show 9.4% students with score 5 out of 14. The highest score is 13, and the lowest is 2. The biggest proportion is staple food group, followed by green leafy vegetable group, egg group, and dairy product. Hal of students consumed salty snack and fried snack also sweets. Around 71.9 respondents have habit to consume supplements such as vitamin C, multivitamin, and multimineral. Based on the study, it concludes that some students already have diverse dietary habit, but there are still some students consume not many types of food, include consuming empty calorie food.